Social Capital, Intellectual Capital On Performance And Competitiveness Of Indonesian Msmes Mediated By Technological Capability And Financial Capability - Novita Susiang, Maria Imelda (Moneta : Journal of Economics and Finance, 2024)
Micro, Small, and Medium-Sized Enterprises (MSMEs) in Indonesia are significant because of their technological prowess, financial know-how, and social and intellectual capital, all of which impact their competitiveness and overall performance. Partial Least Squares Structural Equation Modeling (PLS-SEM) was used in a quantitative survey with 236 MSMEs using a Likert scale to investigate these relationships. Social capital and technological capability, intellectual capital and technological competence, social capital and financial capability, and intellectual capital and financial capability were found to have positive and significant direct correlations. Additionally, the performance and competitiveness of MSMEs were positively impacted by financial and technological skills. The study validated the functions of financial and technological capacities as mediators in the associations between MSME competitiveness and social and intellectual capital. The suggested conceptual framework was supported by the structural model's satisfactory goodness-of-fit indices, which also offered detailed insights into the dynamics of Indonesian MSMEs. The results highlight how important intangible assets and competencies are in determining competitiveness and performance